Analisis Karakteristik dan Kebutuhan Parkir di Pasar Tradisional Dukun, Kabupaten Gresik Jawa Timur - Khoiruddin, Khoiruddin; Hartatik, Nurani; Mawariza, Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research contains parking problems at the Dukun traditional market, Gresik Regency, East Java. From the results of a survey that has been carried out, the on-street parking at the Dukun Traditional Market is unable to accommodate the surge in vehicles visiting the market during peak market hours. The use of on-street parking spaces is not optimal and less regular, resulting in visitors parking their vehicles in random places and creating traffic disruptions. In this research, researchers will use the parking patrol survey method and the parking space inventory survey method to analyze the characteristics, capacity and needs of the Dukun Traditional Market. The aim of this survey is to find out how many parking lots are available in the study area and to calculate the number of parking spaces available at the research location. The research results recorded that the maximum accumulation occurred on Sunday, April 28 2024 with 93 motorbikes and 12 cars, as well as a significant spike at 06.01–07.00 WIB. The maximum motorbike parking volume occurred on Thursday, May 2 2024 with the highest motorbike volume reaching 295 vehicles, and cars reaching 31 vehicles. The longest parking duration for motorbikes is Wednesday, May 1 2024 (267 minutes), and cars are Monday, April 29 2024 (201 minutes). The maximum parking turnover rate occurs on Thursday, May 2 2024 with 4.91 Kend/day/space for motorbikes, and 1.91 Kend/day/space for cars. The maximum parking index for motorbikes and cars is 156%, exceeding 100%, respectively. The current parking space capacity is insufficient, so the Dukun Traditional Market requires additional parking space of 141 m2 for motorbikes and 138 m2 for cars. In conclusion, the current condition of parking spaces exceeds the existing parking capacity.